The Prolonged Tooth Surfaces of Inernal Gear Used in a New Type of Toroidal Drive - 徐晓俊; 张春丽; 董申 (Jixie chuandong)
A method to prolong the tooth surface of a new type of toroidal drive is discussed. The new tooth surface can be prolonged by the normal profile of the internal toroidal surface, or replaced by an equal pitch helical surface. And the approximate meshing condition is also analyzed.